The Evolution of Speech Recognition through Amazon Alexa - Aliyah M. GRAY; Ahmed Y. MAHFOUZ; Kishwar JOONAS (Communications of International Proceedings, 2020)
Over the years, society has put greater emphasis on simplifying everyday tasks and welcoming the idea of a digital world (Juan et. al., 2004). Speech recognition has advanced substantially over the last decade. Today, more people rely on digital assistants to accomplish everyday tasks. Amazon, the world’s largest online retailer, took advantage of the new era of smart assistants and created Alexa, a digital assistant built into Amazon’s services and devices, such as Echo, Dot, and Amazon TV (Wetzel, 2018).  This paper analyzed the growing market of speech recognition software, and its positive and negative impacts on consumers, focusing on Amazon Alexa, which offered a larger range of options over its competitors.
Keywords: Speech Recognition; Ecommerce; Privacy; Personal Assistants.